Hyaluronic acid-curcumin nanoparticles for preventing the progression of experimental autoimmune uveitis through the Keap1/Nrf2/HO-1 signaling pathway - Weiwei Tang; Xiaomin Huang; Yun-Di Yi; Fan Cao; Manli Deng; Jiawei Fan; Zheng-Xuan Jiang; Li-Ming Tao; Xianwen Wang; Lei Shi (Journal of Nanobiotechnology)
Abstract Globally, uveitis is a collection of intraocular inflammatory disorders that affect mainly the uvea, resulting in irreversible blindness and a heavy socioeconomic burden. Excessive autoimmune inflammation and oxidative stress are major drivers that contribute to the initiation and progression of uveitis. Nevertheless, current therapeutic methods for uveitis are limited and are accompanied by several serious adverse effects. Recently, nanotechnology-based antioxidant strategies have provided novel options for the treatment of ocular diseases. Although curcumin (CUR) has prominent antioxidant capacity and reactive oxygen species (ROS) scavenging ability, its low bioavailability and undetermined mechanisms limit its extensive application. This investigation demonstrated that esterified hyaluronic acid-curcumin nanoparticles (HA-CUR NPs) with superior aqueous dispersion exhibited exceptional antioxidant enzyme mimetic activity, incorporating superoxide dismutase (SOD), glutathione (GSH), catalase (CAT), and free radical scavenging ability. Further in vitro and in vivo experimental results validated the protective function of HA-CUR NPs against oxidative stress-induced damage and inflammatory responses, attenuated pathological progression, relieved microvascular damage, and regulated fundus blood flow in retinal vascular networks. This may be attributable to the specific ability of HA-CUR NPs to target the CD44 receptor and activate the Keap1/Nrf2/HO-1 signaling pathway, suggesting a potential mechanism. In summary, this study revealed that HA-CUR NPs, which are composed of a natural product and biomacromolecules with outstanding artificial antioxidant enzyme activities, may be novel agents for effectively and safely treating uveitis and other ROS-related diseases.